2005
DOI: 10.1007/s00402-005-0052-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of intraarticular administration of basic fibroblast growth factor with hyaluronic acid on osteochondral defects of the knee in rabbits

Abstract: Low-dose bFGF with HA was effective for osteochondral repair in rabbits. The significant osteochondral reparative role of bFGF with HA comparing with GM incorporating bFGF might be explained by the potential carrier role of HA and possible synergistic action between these two agents. The combination of HA with bFGF significantly suppressed the side effects resulting from single use of bFGF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(36 citation statements)
references
References 44 publications
0
35
0
1
Order By: Relevance
“…However, there is evidence suggesting that FGF-2 antagonizes proteoglycan synthesis mediated by IGF-I and/or OP-1, can upregulate MMPs, and results in synovial proliferation through protection from apoptosis [25]. Furthermore, animal models suggest intraarticular administration of FGF-2 results in inflammation and osteophyte formation [67] and does not aid in healing of cartilage defects [86]. A more recent rabbit study demonstrated improved healing of osteochondral lesions using a highly porous scaffold soaked in low-dose FGF-2 (10 lg/mL) compared with higher doses of FGF-2 (100 lg/mL) or scaffold without FGF-2, suggesting an inverse dose response [57].…”
Section: Fibroblast Growth Factor Familymentioning
confidence: 95%
“…However, there is evidence suggesting that FGF-2 antagonizes proteoglycan synthesis mediated by IGF-I and/or OP-1, can upregulate MMPs, and results in synovial proliferation through protection from apoptosis [25]. Furthermore, animal models suggest intraarticular administration of FGF-2 results in inflammation and osteophyte formation [67] and does not aid in healing of cartilage defects [86]. A more recent rabbit study demonstrated improved healing of osteochondral lesions using a highly porous scaffold soaked in low-dose FGF-2 (10 lg/mL) compared with higher doses of FGF-2 (100 lg/mL) or scaffold without FGF-2, suggesting an inverse dose response [57].…”
Section: Fibroblast Growth Factor Familymentioning
confidence: 95%
“…Based on the tissue-engineering approach, the use of bioactive agents such as growth factors combined with a three-dimensional scaffold in an appropriate microenvironment to help the body to heal itself has been a focus of attention [10][11][12][13]. The key issue in enhancing regeneration of the injured tissue is seeking an appropriate scaffold to provide a niche for cell recruitment to complete functional restoration.…”
Section: Introductionmentioning
confidence: 99%
“…We compared our study with that of other authors and we noted that most of the studies had good functional results following the PRP injection which compared well with that of ours. [18][19][20][21] All the patients were happy with the outcome following PRP injection and there were no patients who were dissatisfied with the results. The limitations of our study were lack of a placebo/control group and a relatively short follow up period.…”
Section: Discussionmentioning
confidence: 99%